Voices in the Struggle: In Response to "'Reining In' Special Education" - Beth A. Ferri (Disability Studies Quarterly, 2006)
In responding to "'Reining In' Special Education," I explore some of the taken-for-granted assumptions about students with disabilities in The New York Times editorials about special education that Nancy Rice critiques in this issue. Next, I attend to other voices in the editorial page in the form of letters to the editor and editorial pages from the Black press as examples of alternative and competing discourses. Because I contend that editorials are designed not just to persuade, but also to provoke response, I examine ways that these voices talk back and talk with dominant ideologies about special education. And, finally, I examine what these texts are trying to tell readers not only to believe, but also what to do about the so-called "problem" of special education.
Keywords: Special Education; Disability; Media